El Método Peto y la motricidad gruesa en el Inicial 2 de la Unidad Educativa “Miguel Ángel León Pontón” de la ciudad de Riobamba. - Llamuca Solis, Nataly Andrea (2024)
The Gross motor development in children from three to five years old should be adequately stimulated to facilitate the development in the different activities of daily life; although, the development may vary from child to child, playful strategies should be applied for motor learning. The present research project focuses on developing gross motor skills in children of Early Childhood Education 2, through Conductive Pedagogy (Peto Method) in the Educational Unit "Miguel Ángel León Pontón" in Riobamba City. Methodologically, the research has a mixed nature, bibliographic, transversal, descriptive and field type; it has a non-experimental design. It focuses on the study of 27 students of the Initial 2 level, the techniques used were observation and the application of the EDI test that facilitates the statistical study of the research. It was identified that some children present difficulties in their gross motor development, since frustration and sadness were evidenced when not being able to carry out the given order of their activities, concluding that children need their parents to provide them with quality time and unconditional support so that the stage becomes satisfactory.